2016
DOI: 10.1371/journal.pone.0160650
|View full text |Cite
|
Sign up to set email alerts
|

The Chronic Effects of Low- and High-Intensity Resistance Training on Muscular Fitness in Adolescents

Abstract: To compare the effects of high-load, low-repetition maximum (LRM) and low-load, high-repetition maximum (HRM) resistance training regimens on muscular fitness in untrained adolescents. Forty-five untrained adolescents of both sexes (13.7±0.8 years; 161.3±7.5 cm, 56.8±13.4 kg) were randomly assigned into one of three groups: 1) LRM (n = 17): volunteers performed three sets of 4-6-repetition maximum (RM); 2) HRM (n = 16): volunteers performed three sets of 12–15 RM; and 3) control (CON, n = 12). Training was per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 38 publications
2
19
0
1
Order By: Relevance
“…A widespread flaw in the literature relating to RT in female youth is the pooling of performance data of both females and males for analysis within the same studies [8,[78][79][80][81][82][83][84]. In isolation, this is never an acceptable practice in research as it only determines whether a training method is effective independent of any population-specific effects.…”
Section: Discussionmentioning
confidence: 99%
“…A widespread flaw in the literature relating to RT in female youth is the pooling of performance data of both females and males for analysis within the same studies [8,[78][79][80][81][82][83][84]. In isolation, this is never an acceptable practice in research as it only determines whether a training method is effective independent of any population-specific effects.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that, in order to equate volume, the SJ group had to train with a higher number of repetitions in the present study. Whilst many studies have found similar strength gains when training at different repetition ranges (Morton et al, 2011 ; Assunção et al, 2016 ; Fisher et al, 2017 ), there are studies reporting higher strength gains in groups that trained with higher loads and low number of repetitions (Campos et al, 2002 ). According to previous studies, this could be explained by the specificity of the test, since training with a low number of repetitions is closer to what was performed in the 1 RM test (Buckner et al, 2017 ; Gentil, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Adaptations to heavier- or lighter-loads seem similar when repetitions are performed to MF in older adults [40] similarly to findings in both adolescent [41] and young adult populations [42]. However, though supervised high effort RT is effective, Van Roie et al [43] have reported that long term adherence after the initial supervised intervention, whether using heavier- or lighter-loads, is poor.…”
Section: Introductionmentioning
confidence: 67%